LOOKING AT THE LINK BETWEEN EMOTIONAL INTELLIGENCE AND READING COMPREHENSION AMONG SENIOR HIGH SCHOOL STUDENTS - M. Ahlan Firdaus (Edukasi, 2017)
The main purpose of the present study was to empirically investigate the possible correlation between students’ emotional inteligence and thier reading comprehension and students’ emotional intelligence influences their reading comprehension. The participants in the study were 53 the eleventh grade students of SMA Sandika Banyuasin which were selected from two classes consisting of science and social. Reading comprehension test was done to measure students’ reading comprehension by using TOEFL Junior reading comprehension section. Then, USMEQ-i by Yusoff (2010) was administered to the participants to measure their emotional intelligence. SPSS program was run using Pearson Product Moment formula and Regression Analysis to find out the correlation and the influence. The result showed that there was a postive significant correlation between students’ emotional intelligence and reading comprehension with r = .661.Then, there influenced of students’ emotional intelligence on thier reading comprehension with 43.7%.